2008
DOI: 10.1097/sla.0b013e318187a757
|View full text |Cite
|
Sign up to set email alerts
|

National Cancer Institute Designation Predicts Improved Outcomes in Colorectal Cancer Surgery

Abstract: NCI designation is associated with lower risk of postoperative death and improved long-term survival. Possible factors responsible for these benefits include surgeon training, multidisciplinary care, and adherence to treatment guidelines. Studies are underway to elucidate the factors leading to improved patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
96
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 21 publications
7
96
0
5
Order By: Relevance
“…In addition, 5-year survival of 71.5% in the non-CME group is within a close range of the data published by Kube for a German quality assurance program including 31055 patients. The SEER database reports even lower survival rates [14]. Therefore, the effect for CME surgery demonstrated here compares well to the data published so far.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, 5-year survival of 71.5% in the non-CME group is within a close range of the data published by Kube for a German quality assurance program including 31055 patients. The SEER database reports even lower survival rates [14]. Therefore, the effect for CME surgery demonstrated here compares well to the data published so far.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, a comprehensive center must also demonstrate professional and public education and outreach capabilities, including the dissemination of clinical and public health advances in the communities it serves.^ [2] NCIdesignated cancer centers are credited with providing multidisciplinary and state of the art cancer treatment and expertise in rare cancers [2]. Patients treated at NCI-designated cancer centers are shown to experience lower cancer surgical mortality and superior treatment outcomes [3][4][5]. However, the use of treatment services provided by NCI-designated comprehensive cancer centers (NCI-CCCs) by ethnic minority patients has not been extensively studied [6].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Given the increasing regionalization of RC to high-volume, academic centres, 19 we felt it was important to validate this move by comparing outcomes at teaching and non-teaching institutions and particularly to confirm whether improved outcomes are seen at NCI-designated CC, as has already been shown for other major oncologic surgery. 11,12 Our analysis raised several noteworthy findings. Firstly, to our knowledge, we are the first to demonstrate superior perioperative outcomes after RC at centres with NCI designation.…”
Section: Discussionmentioning
confidence: 80%
“…10 However, there are only a few reports comparing postoperative outcomes after major oncologic surgery between NCI-designated CC and those without such designation. 11,12 These studies analyzed historic cohorts of patients treated in the previous decade and found that postoperative mortality rates after visceral 11,12 and thoracic surgery were lower in NCI-designated CC. 11,12 Importantly, no difference in operative mortality was seen for RC, 11 and in any case, perioperative outcomes were not assessed as the primary endpoint in either study.…”
Section: Introductionmentioning
confidence: 99%